Chromosomal evidence for a new cryptic species of black fly in the Simulium praelargum complex (Diptera: Simuliidae) from West Bengal, India - Thapa, Sachin; Adler, Peter H.; Chhetri, Shailika; Varma, Rakesh; Henry, Willie (Zootaxa, 2017)
Analyses of polytene chromosomes revealed a new cryptic species of black fly, Simulium praelargum “IL”, in the Simulium (Nevermania) feuerborni group from Darjeeling, West Bengal, India. This new species occurred sympatrically with two other previously recognized species in the S. praelargum complex: Simulium praelargum Datta sensu stricto and Simulium praelargum “IIIL-1.2”. Chromosome arms IS, IIS, IIL, and IIIS of the new species showed no differences in banding patterns, compared with the sequences in Simulium praelargum s. s. and Simulium praelargum “IIIL-1.2”. Chromosome arm IIIL of the new species was identical to that of S. praelargum s. s., but differed from that of S. praelargum “IIIL-1.2” by two fixed inversions. Chromosome arm IL of the new species differed from that of both species by four fixed inversions: IL-1, IL-2, IL-3, and IL-4. The new species and S. praelargum s. s. lacked a chromocenter, which was present in S. praelargum “IIIL-1.2”. Sex chromosomes of the new species were cytologically undifferentiated (X0X0, X0Y0) and all specimens were monomorphic for autosomal inversion polymorphisms. Speciation in the S. feuerborni group, unlike in many other simuliid taxa, did not involve cytological differentiation of sex chromosomes.